THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE FUTURE OF PROFESSIONAL TRANSLATION (Ustozlar uchun, 2026)
This article examines the transformative influence of Artificial Intelligence (AI) and Neural Machine Translation (NMT) on the professional translation landscape. It explores the transition from traditional human-led translation to a hybrid model characterized by Human-in-the-Loop (HITL) processes. The study analyzes the ethical, economic, and qualitative implications of AI integration, concluding that while automation handles volume, the nuanced cognitive expertise of professional translators remains indispensable for high-stakes communication.